The effect of pre-exercise alkalosis on lactate/pH regulation and mitochondrial respiration following sprint-interval exercise in humans - Thomas, Claire; Delfour‐Peyrethon, Rémi; Lambert, Karen; Granata, Cesare; Hobbs, Thomas; Hanon, Christine; Bishop, David J. (Frontiers in Physiology, 2023)
Purpose: The purpose of this study was to evaluate the effect of pre-exercise alkalosis, induced via ingestion of sodium bicarbonate, on changes to lactate/pH regulatory proteins and mitochondrial function induced by a sprint-interval exercise session in humans. Methods: On two occasions separated by 1 week, eight active men performed a 3 × 30-s all-out cycling test, interspersed with 20 min of recovery, following either placebo (PLA) or sodium bicarbonate (BIC) ingestion. Results: Blood bicarbonate and pH were elevated at all time points after ingestion in BIC vs PLA (p < 0.05). The protein content of monocarboxylate transporter 1 (MCT1) and basigin (CD147), at 6 h and 24 h post-exercise, and sodium/hydrogen exchanger 1 (NHE1) 24 h post-exercise, were significantly greater in BIC compared to PLA (p < 0.05), whereas monocarboxylate transporter 4 (MCT4), sodium/bicarbonate cotransporter (NBC), and carbonic anhydrase isoform II (CAII) content was unchanged. These increases in protein content in BIC vs. PLA after acute sprint-interval exercise may be associated with altered physiological responses to exercise, such as the higher blood pH and bicarbonate concentration values, and lower exercise-induced oxidative stress observed during recovery (p < 0.05). Additionally, mitochondrial respiration decreased after 24 h of recovery in the BIC condition only, with no changes in oxidative protein content in either condition. Conclusion: These data demonstrate that metabolic alkalosis induces post-exercise increases in several lactate/pH regulatory proteins, and reveal an unexpected role for acidosis in mitigating the loss of mitochondrial respiration caused by exercise in the short term.